2006
DOI: 10.1200/jco.2006.05.7059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-Dose Busulfan Plus Melphalan As Consolidation in Metastatic Ewing Tumors: A Study by the Société Française des Cancers de l'Enfant

Abstract: Compared with conventional chemotherapy, HDCT may yield benefits for patients with lung-only metastases or bone metastases. These results warrant confirmation in a randomized trial and provide part of the background data for the ongoing Euro-Ewing study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
91
3
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 25 publications
1
91
3
4
Order By: Relevance
“…Prognostic factors (age, initial tumour volume, number of bone metastases, bone marrow and lung involvement) had allowed clinicians to define a prognostic score in this population. 6,7 The 3-year EFS rate was 50, 25 and 10% for a score of o 3, from 3 to 5 and for a score ⩾ 5, respectively. 6 The benefit of a myeloablative regimen in terms of outcome has been demonstrated in several tumour types with high sensitivity to HDC (for example, high-risk neuroblastomas).…”
mentioning
confidence: 99%
“…Prognostic factors (age, initial tumour volume, number of bone metastases, bone marrow and lung involvement) had allowed clinicians to define a prognostic score in this population. 6,7 The 3-year EFS rate was 50, 25 and 10% for a score of o 3, from 3 to 5 and for a score ⩾ 5, respectively. 6 The benefit of a myeloablative regimen in terms of outcome has been demonstrated in several tumour types with high sensitivity to HDC (for example, high-risk neuroblastomas).…”
mentioning
confidence: 99%
“…Proteins are considered the hallmark of genetic alterations. Global mRNA expression studies are often performed to follow these changes [29,[30][31][32][33][34]. However, recent comparative studies of mRNA and protein expression in tumor cells revealed only a subset of mRNA correlated with protein abundance [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…Wide excision of tumors in conjunction with multiagent chemotherapy now provides 5-year diseasespecific survivals ranging from 60% to 80% in patients with localized high-grade sarcomas [2,5,27]. Despite this success, the outcomes of patients who have metastatic disease at diagnosis or those with tumors showing a poor response to chemotherapy are still unsatisfactory (5-year disease-specific survival rates, 20%-40%), even with doseintensive or high-dose chemotherapy [9,18,19,33]. For improving the prognosis of patients with these difficult-totreat sarcomas, it is imperative to develop new targeted therapeutic strategies based on an understanding of the biologic mechanisms underlying the metastasis and chemoresistance of these tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year EFS for lung-only metastases was 52%, and this compares favorably with the 34% 8-year EFS reported in 32 patients with lung-only metastases reported with chemotherapy. 3 Data regarding the site of metastases are not given in the IBMTR report, and this could be important, as patients with other sites of disease fared much worse in the report by Oberlin et al 4 In conclusion, valid comparisons between chemotherapy and myeloablative therapy can be made only on the basis of a randomized trial. We share the desire with Gardner et al to see the results of the randomized Euro EWING 99 study.…”
mentioning
confidence: 99%
“…A prospective study that used etoposide and ifosfamide in induction and consolidation with myeloablative therapy with busulfan and melphalan was reported by Oberlin et al 4 Ninety-seven newly diagnosed patients with metastatic Ewing sarcoma were enrolled and the 5-year EFS was 37%. The 5-year EFS for lung-only metastases was 52%, and this compares favorably with the 34% 8-year EFS reported in 32 patients with lung-only metastases reported with chemotherapy.…”
mentioning
confidence: 99%